Learning Under Neoliberalism Ethnographies of Governance in Higher Education (Higher Education in Critical Perspective: Practices and Policies, 2015)
As part of the neoliberal trends toward public-private partnerships, universities all over the world have forged more intimate relationships with corporate interests and more closely resemble for-profit corporations in both structure and practice.  These transformations, accompanied by new forms of governance, produce new subject-positions among faculty and students and enable new approaches to teaching, curricula, research, and everyday practices. The contributors to this volume use ethnographic methods to investigate the multi-faceted impacts of neoliberal restructuring, while reporting on their own pedagogical responses, at universities in the United States, Europe, and New Zealand